2011
DOI: 10.1590/s0103-50532011000200007
|View full text |Cite
|
Sign up to set email alerts
|

Bioconcentration of Cd and Pb by the river crab Trichodactylus fluviatilis (crustacea: decapoda)

Abstract: Foi avaliada a bioconcentração de cádmio e chumbo pelo caranguejo fluvial Trichodactylus fluviatilis. Trinta animais foram expostos a 200 mg L -1 de cádmio e chumbo por 7, 14 e 21 dias. Após dissecação e digestão nitro-perclórica, os metais foram determinados nas brânquias, hepatopâncreas e músculo por espectrometria de emissão óptica com plasma acoplado indutivamente. O chumbo foi detectado apenas nas brânquias, sem diferenças significativas entre diferentes períodos de exposição. O cádmio foi encontrado em t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Franchi et al, for example, reported that Cd occurs in free form in the gills and is sequestered (likely with metallothioneins) in the hepatopancreas, suggesting that the free Cd in the gills is later deposited in other tissues. [10] Likewise, Bjerregaard has demonstrated that Cd present in the hepatopancreas is transported there by haemolymph from the gills. result of their direct exposure to the surrounding environment, the gills of crustaceans also tend to accumulate high concentrations of certain metals, such as Cd [12] and Pb.…”
Section: Discussionmentioning
confidence: 99%
“…Franchi et al, for example, reported that Cd occurs in free form in the gills and is sequestered (likely with metallothioneins) in the hepatopancreas, suggesting that the free Cd in the gills is later deposited in other tissues. [10] Likewise, Bjerregaard has demonstrated that Cd present in the hepatopancreas is transported there by haemolymph from the gills. result of their direct exposure to the surrounding environment, the gills of crustaceans also tend to accumulate high concentrations of certain metals, such as Cd [12] and Pb.…”
Section: Discussionmentioning
confidence: 99%